COMPARATIVE STUDY OF THE GROWTH AND YIELD OF THREE CULTIVATED Pleurotus SPECIES ON SELECTED TROPICAL TREES SAWDUSTS (2015)
The quest to boost dietary protein production from readily available and affordable sources is ever increasing in developing countries. The indigenous edible Pleurotus species (oyster mushrooms), which grow naturally on wood wastes, are potential protein supplements. However, little information is available on the usage of selected tropical trees for optimum mushroom cultivation. Therefore, this research was designed to investigate the growth and yield of oyster mushrooms on sawdust of selected tropical trees. Mature stems of Mangifera indica L. (PTBG0000039360), Senna siamea Lam. (BISH0000032830) and Azadirachta indica A. Juss (BISH0000015188) were harvested and identity authenticated at the National Horticultural Research Institute (NIHORT), Ibadan. The samples were air-dried, separately milled into sawdust, composted and used as three substrates. The fourth substrate was the mixed bed derived from the mixtures of the three substrates in ratio 1:1:1 by weight. Three mushroom species (Pleurotus ostreatus, P. pulmonarius and P. tuber-regium) were collected from Mycology Unit, NIHORT. A total of 108 polyethylene substrate bags (27 for each substrate) were filled with 300 g of the sawdust, each tightly packed, sterilised and inoculated with 30 g each of mushroom spawn. Mycelial growth was determined using standard method. Fruiting body production was obtained for the three mushrooms on all the substrates and sclerotia weight recorded at different Weeks of Composting Intervals (WCI) of 4, 8 and 12. Biological and production efficiencies were determined using mathematical methods. The experiment was a 4 x 3 x 3 factorial arrangement laid out in a complete randomised design with three replicates each. The data were analysed using descriptive statistics and ANOVA at p =0.05. The longest and the shortest mycelial extensions (13.3 and 4.6 cm) were observed in P. pulmonarius grown on A. indica at 4WCI and 8WCI respectively. At 12WCI, the highest Fruit Weight (FW) of 86.8±1.2 g for P. pulmonarius was observed on S. siamea which was not significantly different from P. ostreatus (84.9±1.2 g) on M. indica. The most significant Biological Efficiencies (BE) of 82.7% and 80.9% for P. pulmonarius and P. ostreatus at 12WCI respectively were observed on S. siamea and M. indica. At 12WCI, the Production Efficiency (PE) was highest (42.8%) for P. ostreatus on M. indica and 41.1% for P. pulmonarius on S. siamea. Also, the highest mean sclerotia weight of 42.1±0.9 g was obtained for P. tuber-regium on M. indica at 12WCI. However, at 4WCI, the least FW (13.7±0.1 g) was in P. pulmonarius cultivated on S. siamea while the least BE (13.0%) was observed for P. pulmonarius on S. siamea. Also, the least PE value of 4.9% for P. pulmonarius was observed on S. siamea while the least sclerotia weight of 9.0±0.6 g was obtained on mixed bed. The longer the decomposition period of the substrate, the more significant was the yield. The best substrate for the production of fruiting body of Pleurotus ostreatus and sclerotia of Pleurotus tuber-regium was Mangifera indica while Senna siamea was most suitable for Pleurotus pulmonarius. Keywords: Biological and production efficiencies, Composting intervals, Oyster mushrooms, Tropical trees sawdust Word count: 488